Anticoagulation Control in Different Ethnic Groups Receiving Vitamin K Antagonist for Stroke Prevention in Atrial Fibrillation - Zawawi, Nur Azyyati; Abdul Halim Zaki, Izzati; Ming, Long Chiau; Goh, Hui Poh; Zulkifly, Hanis Hanum (Frontiers in Cardiovascular Medicine, 2021)
Vitamin K antagonist such as warfarin reduces the risk of stroke in atrial fibrillation (AF) patients. Since warfarin has a narrow therapeutic index, its administration needs to be regularly monitored to avoid any adverse clinical outcomes such as stroke and bleeding. The quality of anticoagulation control with warfarin therapy can be measured by using time in therapeutic range (TTR). This review focuses on the prevalence of AF, quality of anticoagulation control (TTR), and adverse clinical outcomes in AF patients within different ethnic groups receiving warfarin therapy for stroke prevention. A literature search was conducted in Embase and PubMed using keywords of “prevalence”, “atrial fibrillation”, “stroke prevention”, “oral anticoagulants”, “warfarin”, “ethnicities”, “race” “time in therapeutic range”, “adverse clinical outcome”, “stroke, bleeding”. Articles published by 1st February 2020 were included. Forty-one studies were included in the final review consisting of AF prevalence (n=14 studies), time in therapeutic range (n=19 studies), adverse clinical outcome (n=8 studies) within different ethnic groups. Findings indicate a higher prevalence of AF but better anticoagulation control among the Whites as compared to other ethnicities. Of note, non-whites had a higher risk of strokes and bleeding outcomes while on warfarin therapy. Addressing disparities in prevention and healthcare resource allocation could potentially improve AF-related outcomes in minorities.